If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -1x = 33(x + 7) Reorder the terms: 17 + -1x = 33(7 + x) 17 + -1x = (7 * 33 + x * 33) 17 + -1x = (231 + 33x) Solving 17 + -1x = 231 + 33x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33x' to each side of the equation. 17 + -1x + -33x = 231 + 33x + -33x Combine like terms: -1x + -33x = -34x 17 + -34x = 231 + 33x + -33x Combine like terms: 33x + -33x = 0 17 + -34x = 231 + 0 17 + -34x = 231 Add '-17' to each side of the equation. 17 + -17 + -34x = 231 + -17 Combine like terms: 17 + -17 = 0 0 + -34x = 231 + -17 -34x = 231 + -17 Combine like terms: 231 + -17 = 214 -34x = 214 Divide each side by '-34'. x = -6.294117647 Simplifying x = -6.294117647
| 6-2(3x-4)=12 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | A=2x+2y | | 3t+4=16 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | A=2x+2y | | -6x^2+5x+6=1.41666 | | -3+6x=5x-13 | | 8y-9=2-88yip | | 6/5x-8=3/4x | | 27+2x+5+3x-4=180 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | ax^2+5x+6=1.41666 | | 6/5x-8=3/4x | | 6/5x-8=3/4x | | -3+6x=5x-13 | | -3+6x=5x-13 | | 9(x-8)+28=9x-44 | | 6/7*7/8 | | 27+2x+5+3x-4=180 | | -9(9+u)-2u=-10 | | 3t+4+t=6 | | (3t^4)(-2t)(5t^6)=x | | -9(9+u)-2u=-10 | | -3+6x=5x-13 | | 6/7*7/8 | | 6/7*7/8 | | 5x+10y=-20findx | | x=56-3x | | 3t+4+t=6 | | 25-2x=-(-6+7) | | 6w-5= |